A peripheral neuroectodermal tumor of the vulva. - Paredes, E (1995)
A case of malignant peripheral neuroectodermal tumor occurring in the vulva of a 29-year-old woman is reported. It is a rare malignant tumor with aggressive biological behavior belonging to a wide group, the so-called small round-cell tumors. The patient is well and free of disease 8 months after surgery, chemotherapy and radiation therapy.